A New Application of Calculus and Risk Analysis to Cost-Volume-Profit Changes. - Morrison, Thomas A.; Kaczka, Eugene (The Accounting Review, 1969)
This article discusses a new application of calculus and risk analysis of cost-volume-profit changes. Differential calculus has recently been applied to some cost-volume-profit situations as an extension of break-even analysis to find maximum profit levels when cost and/or revenue behavior is curvilinear. All companies consider the effect that changes in selling prices will have on the sales of their product. They are also laboring under a constant cost-push pressure to increase prices. Therefore, companies must forecast expected volume for the various changes in sales price. Then they must determine whether or not such changes will be profitable. The traditional method of approaching these problems is to select several discrete changes in sales prices, forecast new levels of sales at these points, and select the most profitable alternative. All managerial accounting texts explain this method but go no further. This article extends the usual approach by considering a continuum of price changes and incorporating risk in the analysis.